Bridging the Separation Between Studies of the Biophysics of Natural and Built Marine Canopies - Stevens, Craig; Plew, David (Frontiers in Marine Science, 2019)
We argue that there is a separation between studies of the biophysics of natural and “built” marine canopies. Here, by “built” we specifically refer to floating, suspended aquaculture canopies. These structures, combining support infrastructure and crop, exhibit several unique features relative to natural marine canopies, in that they take a particular species, suspend them in spatially structured, mono-cultured arrangement and then induce a systematic harvest cycle. This is in contrast to natural canopies that are irregular and variable in form, have natural recruitment and growth, and sustain some level of biodiversity and more exposed to climate extremes. We synthesize published work to identify the points of difference and similarity with natural canopy studies. This perspective article identifies four main themes relating to (i) key scales, (ii) structural configuration, (iii) connections between biology and physics and (iv) connecting natural and built canopy science. Despite clear differences between natural and built canopies, they have more in common than not but and we suggest that both sub-fields would benefit from better connection across the divide.